MYC-nick promotes cell migration by inducing fascin expression and Cdc42 activation - Anderson, Sarah; Poudel, Kumud Raj; Roh-Johnson, Minna; Brabletz, Thomas; Yu, Ming; Borenstein-Auerbach, Nofit; Grady, William N.; Bai, Jihong; Moens, Cecilia B.; Eisenman, Robert N.; Conacci-Sorrell, Maralice (Proceedings of the National Academy of Sciences of the United States of America, 2016)
MYC-nick is a cytoplasmic, transcriptionally inactive member of the MYC oncoprotein family, generated by a proteolytic cleavage of full-length MYC. MYC-nick promotes migration and survival of cells in response to chemotherapeutic agents or withdrawal of glucose. Here we report that MYC-nick is abundant in colonic and intestinal tumors derived from mouse models with mutations in the Wnt, TGF-?, and PI3K pathways. Moreover, MYC-nick is elevated in colon cancer cells deleted for FBWX7, which encodes the major E3 ligase of full-length MYC frequently mutated in colorectal cancers. MYC-nick promotes the migration of colon cancer cells assayed in 3D cultures or grown as xenografts in a zebrafish metastasis model. MYC-nick accelerates migration by activating the Rho GTPase Cdc42 and inducing fascin expression. MYC-nick, fascin, and Cdc42 are frequently up-regulated in cells present at the invasive front of human colorectal tumors, suggesting a coordinated role for these proteins in tumor migration.
EVALuna2:10218